HUBUNGAN ANTARA REGULASI DIRI DALAM BELAJAR DENGAN PRESTASI BELAJAR MAHASISWA FKIP JURUSAN PENDIDIKAN BAHASA INGGRIS UNBARI - Yurni Yurni (Universitas Batanghari Jambi, 2013)
The aim of this research was to find out whether there was a correlation between self regulated in learning and learning achievement of English department student at FKIP Unbari. Subject of this research was 70 students (30 male and 40 female) collected by purposive random sampling technique. There were 22 statement of self regulated learning distributed to subject. Statistical method pearson correlation was used to analyzed the correlation between two variable. It was found that coefficient correlation rxy -049 with significance value 0.688 (p≥0,01). It mean there was no correlation between self regulated in learning and learning achievement, hypothesis was rejectedKey Word: self regulated learning, learning achievement